A new approach for accurate mass assignment on a multi-turn time-of-flight mass spectrometer. Issue 6 (December 2017) - Hondo, Toshinobu; Jensen, Kirk R; Aoki, Jun; Toyoda, Michisato
A simple, effective accurate mass assignment procedure for a time-of-flight mass spectrometer is desirable. External mass calibration using a mass calibration standard together with an internal mass reference (lock mass) is a common technique for mass assignment, however, using polynomial fitting can result in mass-dependent errors. By using the multi-turn time-of-flight mass spectrometer infiTOF-UHV, we were able to obtain multiple time-of-flight data from an ion monitored under several different numbers of laps that was then used to calculate a mass calibration equation. We have developed a data acquisition system that simultaneously monitors spectra at several different lap conditions with on-the-fly centroid determination and scan law estimation, which is a function of acceleration voltage, flight path, and instrumental time delay. Less than 0.9 mDa mass errors were observed for assigned mass to charge ratios ( m/z ) ranging between 4 and 134 using only 40 Ar + as a reference. It was also observed that estimating the scan law on-the-fly provides excellent mass drift compensation.